(untitled) (Brazilian Journal of Oceanography, 2011)
Despite the long history of the development of artificial structures in NSW estuaries there are no studies that provide any comprehensive scientific evaluation of post-deployment goals. We assessed the effectiveness of estuarine artificial reefs as a fisheries enhancement initiative; described the diversity and abundance of species associated with them, and detailed the patterns of colonization and community development associated with an artificial reef deployment in Lake Macquarie, a large coastal barrier lagoon on the southeast coast of Australia. Six artificial reefs (one artificial reef group), constructed from artificial reef units (Reef Balls®), were deployed in December 2005 and sampled six times per season over two years using baited remote underwater video (BRUV). Colonization of the artificial reef group was relatively rapid with the majority of species identified over the two-year study period observed within the first year post-deployment. Overall, 27 species from 17 families were identified. Key colonising species included Pelates sexlineatus (Terapontidae), Acanthopagrus australis (Sparidae), Pagrus auratus (Sparidae) and Rhabdosargus sarba (Sparidae). Species richness showed evidence of potential seasonal fluctuations, being higher in warm water months (Summer/Autumn), and lower in the colder water months (Winter/Spring), while species diversity increased significantly with reef age. Fish assemblage composition remained relatively stable after the first year of sampling, with few discernible patterns in assemblage structure evident after the first year. Distinct separation in reef age groupings was evident during the second year of sampling; a pattern primarily driven by a decrease in abundance of P. sexlineatus, a result of the isolated nature of the artificial reefs and the interrelated effects of density dependence and predation.